2005
DOI: 10.1021/la047495g
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous and Gaseous Adsorption from Montmorillonite−Carbon Composites and from Derived Carbons

Abstract: Clay-carbon composites and the carbons derived from demineralization of the clay template were examined for their aqueous adsorption properties (2,4,6-trichlorophenol and methylene blue) and for their gas adsorption/separation abilities regarding CO(2), CH(4), and N(2) gases. The sorption results are discussed in relation with their structural properties (surface area, pore width and volume, and surface chemistry). It was found that the properties of the adsorbents depend highly on the synthetic route, for ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 33 publications
3
24
0
7
Order By: Relevance
“…Previous studies have shown that this type of nanocomposites has quite wide applications. For example, they can be directly used as adsorbents for organic compounds (Bakandritsos et al, 2005;Putyera et al, 1994), and they have also been used as precursor for synthesizing derivative nanomaterials (Bandosz et al, , 1996Leboda et al, 2005;Zhang et al, 2012). One of the interesting nanomaterials is the graphene-like material, which can be obtained by removing Mt layers from the nanocomposites (Bandosz et al, , 1996Leboda et al, 2005).…”
Section: Elemental Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that this type of nanocomposites has quite wide applications. For example, they can be directly used as adsorbents for organic compounds (Bakandritsos et al, 2005;Putyera et al, 1994), and they have also been used as precursor for synthesizing derivative nanomaterials (Bandosz et al, , 1996Leboda et al, 2005;Zhang et al, 2012). One of the interesting nanomaterials is the graphene-like material, which can be obtained by removing Mt layers from the nanocomposites (Bandosz et al, , 1996Leboda et al, 2005).…”
Section: Elemental Analysis Resultsmentioning
confidence: 99%
“…One example is the insitu synthesis of 2D carbon nanomaterials within Mt interlayer spaces. Thanks to its layered structure, expandable interlayers, and chemically inert siloxane surface, Mt has been considered as ideal template for insitu transforming pre-intercalated carbon-rich organic compounds into 2D carbon nanomaterials (Bakandritsos et al, 2004(Bakandritsos et al, , 2005BarataRodrigues et al, 2003;Sakintuna and Yurum, 2005;Xu et al, 2013;Zhang et al, 2012). Polymers have most often been used as precursor in previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CH 4 and N 2 have often been used as probe molecules to evaluate the gas adsorption capacity and porosity of Mt and its derivatives (Bakandritsos et al, 2005;Barrer and Reay, 1957;Maes et al, 1997;Volzone and Ortiga, 2004). The estimation parameters of Mt based on N 2 and CH 4 adsorption are comparable (Volzone and Ortiga, 2004) because i) both CH 4 and N 2 are nonpolar molecules and are physically adsorbed on Mt, and ii) the kinetic diameter of CH 4 (0.38 nm) is similar to that of N 2 (0.35 nm).…”
Section: Discussionmentioning
confidence: 99%
“…The former band indicated the incomplete dehydroxylation at 700°C, which was also reported by previous studies (Kloprogge et al, 1999); the later may result from water molecules readsorbed (during the sample preparation process for FTIR characterization) by the abundant micropore and strong hydrophilicity of Al 13 -Mt-700 as discussed above. On the other hand, the absorption band at 1588 cm −1 for MB-Mt-700 arose from the C_C stretching vibration (Bakandritsos et al, 2005;Szabó et al, 2005), implying the formation of graphene-like (sp 2 -hybridized) carbon within the interlayer space.…”
Section: Ftir Spectroscopy Characterizationmentioning
confidence: 99%